Care in konsensuell-nichtmonogamen Beziehungsnetzwerken Sorgende Netze jenseits der Norm - Raab, Michael (Verlag Barbara Budrich, 2019)
Polyamory and other non-monogamous relationships are becoming increasingly visible. They are often seen as a more self-determined and gender-equitable alternative to conventional marriage and family. The Marxist, feminist and intersectionally well-founded qualitative study shows what characterizes these relationship networks. Is it possible in the area of ​​care to implement the self-imposed emancipatory claims?